In Vivo 3-D Dose Verification Using PET/CT Images After Carbon-Ion Radiation Therapy - Sun, Lining; Hu, Weigang; Lai, Songtao; Shi, Leijun; Chen, Junchao (Frontiers in Oncology, 2021)
Objective To investigate the usefulness of positron emission tomography (PET) image obtained after carbon-ion irradiation for dose verification in carbon-ion radiotherapy Methods and Materials An anthropomorphic head phantom was used in this study. Three cubes with volumes of 1 ml, 4 ml and 10 ml were contoured as targets in the phantom CT through treatment planning system (TPS). Treatment plans with sixprescriptions from 2.5 Gy to 10Gy（2.5Gy,3Gy,5Gy,6Gy,8Gy and 10Gy, effective dose） were designed and delivered by 90-degree fixed carbon-ion beams, respectively. After irradiation of the phantom, a PET/CT scanning was performed to fuse the treatment planning CT image with the PET/CT image. The relationship between target volume and the standard uptake value (SUV) in PET/CT was evaluated for corresponding plan prescription. The MIM Maestro software was used for the image fusion and data analysis. Results SUV in the target had an approximate linear relationship with effective dose. The same effective dose could generate the roughly equal SUV for different target volumes (p< 0.05). Conclusions It is feasible to verify the actual 3D dose distribution of carbon-ion radiotherapy by the approach in this study.